EFFECT OF INFORMATION SHARING TOWARD EQUILATERAL AGILITY WITH KNOWLEDGE EXPLOITATION AND EXPLORATION AS AN INTERVENING VARIABLE - Nurcholis, Lutfi; Cahyono, Budhi (Jurnal Aplikasi Manajemen, 2019)
This paper aims to investigate the effect of information sharing toward responsiveness, operational flexibility and business relationship with knowledge exploitation and exploration. Data were collected from 201 SMEs in Indonesia and were analyzed by using Structural Equation Modeling (SEM). The result shows that Information sharing significantly affect knowledge exploitation and responsiveness, knowledge exploration significantly affect business relationship and operational flexibility, knowledge exploitation significantly affect operational flexibility. Furthermore, information sharing does not significantly affect knowledge exploration, operational flexibility and business relationship, knowledge exploration does not significantly affect responsiveness and knowledge exploitation does not significantly affect business relationship and responsiveness. Recommendations for future researchers are expected to apply to the business sector with a larger scale and wider geographical area.